From Sandwich to Santara: Frivolously Serious Publications by Lithuanian Students in the US - Dapkutė, Daiva (Knygotyra, 2020)
Following World War II, Lithuanian academic youth, who found themselves and continued their studies at the US universities, joined various organizations, as a result active social, cultural and societal life of students took place. The main organizations uniting Lithuanian students in the US (the Lithuanian Student Union, the Catholic Student Union Ateitis, the Academic Scout Movement, the Lithuanian student group Santara) perceiving the impact of information, took special care of their press publications that had become one of the main tools in helping to gather academic youth, to disseminate organizational / ideological ideas not only among students but also among the wider society.This article presents and analyzes one-time and continuous publications published by Lithuanian students in the US, which have not received wider attention from researchers so far. The main attention is focused on the publications published by one of the organizations - Lithuanian student group Santara (since 1957 Santara-Šviesa Federations), as well as the analysis of the publications published by other organizations - the Lithuanian Student Union, the Academic Scout Movement, the Catholic Student Union Ateitis - their repertoire, content, significance in student life. The study covers the period of the 1950s-1960s allowing the observation of the most intensive activity of Lithuanian students in the US, their active participation in the public life of the Lithuanian community and a great deal of attention to own press problems. At that time, the main Lithuanian student organizations published various publications for their members and the general public: from one-time (humorous, occasional or camp) publications, newsletters intended for members only to successful and none too successful attempts to publish their own periodicals.The Lithuanian American Student Union established in 1951 for the purpose of informing members since March 1954 began publishing Lietuvių Studentų Sąjungos JAV biuletenis (the US Newsletter of the Lithuanian Student Union), which soon became a serious student magazine, Studentų gairės (Student Guidelines), published by in a printing house, and from 1954, students launched the English-language magazine Lituanus, which became an academic magazine for foreigners, published to this day. Ideological organizations (scouts, members of Ateitis and Santara), which had student columns in the major Lithuanian press, and published various one-time or continuous publications, took a very active part in the press work. The organizations had their own newsletters: the Academic Scout Movement (ASM) published the newsletter Ad meliorem for ASM members, the Catholic Student Union Ateitis in Cleveland since 1951 published Gaudeamus, in 1957-1961, Santara published the newsletter Žvilgsniai (Glances). Newsletters of separate columns (such as New Yorko Santara - New York Santara) also appeared, although they were irregular, often only published for a short time. Various one-off publications were popular among young people: occasional, humoristic (e. g. Krambambulis, Sumuštinis - Sandwich), a gathering or a camp publications (Arielkon – To Homemade Vodka, Niekšybės paslaptis - The Secret of Villainy, Po nemigos - After Insomnia etc.). These publications were self-published in a very small circulation and distributed only among members of the organization. Many of them have not survived or if survived are kept by private archives or archival institutions. The place of publication and circulation of these publications were usually not indicated, unmarked; publishers, editors, authors of articles and illustrations are left unknown, periodicity of publications and even the number of published publications – unclear.The content of most student published publications was analogous. The publications contained a variety of information – from serious texts analyzing issues on Lithuanian identity and social activities relevant to the young generation of the diaspora, as well as brief organizational information, humour columns, photographs and friendly banter addressed to self and colleagues. Despite their quality and sometimes seemingly insignificant content, these publications become an important, often the only one source revealing to researchers the peculiarities of the little-known American youth camping, the peculiarities of student social and community life.
Keywords: the US; diaspora; Lithuanians; students; press; publications; the Lithuanian Student Union; scouts; members of the Catholic Student Union Ateitis; Santara-Šviesa